The Decreasing Trend in U.S. Cash Effective Tax Rates: The Role of Growth in Pre-Tax Income - Edwards, Alexander; Kubata, Adrian; Shevlin, Terry (The Accounting Review, 2021)
ABSTRACT We develop a linear corporate tax function where taxes paid are regressed on pre-tax income and an intercept. We show that if the intercept is positive, cash ETRs are a convex function of pre-tax income. We present large-sample evidence consistent with this ETR convexity. Thus, although firms may have stable linear tax functions (i.e., constant parameters in the linear tax model) representing stable tax avoidance behavior, ETRs can change over time because of growth in pre-tax income. Consequently, simply examining changes (or differences) in cash ETRs is nondiagnostic about whether tax avoidance has changed over time (or differs across firms). We illustrate our argument by showing that all of the observed downward trend in cash ETRs documented by Dyreng et al. (2017) can be explained by growth in pre-tax income. The wholesale concern about increased tax avoidance over time might be overstated. Data Availability: Data are available from the public sources cited in the text. JEL Classifications: G39; H20; H25; H26.